2013
DOI: 10.1179/1743281213y.0000000131
|View full text |Cite
|
Sign up to set email alerts
|

Development of mould fluxes based on lime–alumina slag system for casting high aluminium TRIP steel

Abstract: With excellent strength and ductility properties, transformation induced plasticity (TRIP) steels are superior to ordinary commercial steels and have great application potential in the automobile industry. However, the continuous casting of TRIP steels is associated with challenges owing to its high aluminium content, approximately 0?5-1?8%. The reaction of aluminium near the steel/slag interface continuously changes the basicity of conventional lime-silica based mould fluxes causing variation in the flux phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 8 publications
0
23
0
1
Order By: Relevance
“…The high concentrations of SiO 2 react with Al to yield controlled performance of the spent CaO–SiO 2 –Al 2 O 3 mold fluxes (SiO 2 ~10–30 mol%, Al 2 O 3 ~5–15 mol%) to meet the demands for high‐Al steels casting . The second method is based on nonreactive mold fluxes, which utilizes novel developed CaO–Al 2 O 3 mold fluxes with concentrations higher in Al 2 O 3 and lower in SiO 2 (SiO 2 < 10 mol%, Al 2 O 3 > 15 mol%) to suppress the slags/steel reaction . Both strategies, however, have their advantages and drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…The high concentrations of SiO 2 react with Al to yield controlled performance of the spent CaO–SiO 2 –Al 2 O 3 mold fluxes (SiO 2 ~10–30 mol%, Al 2 O 3 ~5–15 mol%) to meet the demands for high‐Al steels casting . The second method is based on nonreactive mold fluxes, which utilizes novel developed CaO–Al 2 O 3 mold fluxes with concentrations higher in Al 2 O 3 and lower in SiO 2 (SiO 2 < 10 mol%, Al 2 O 3 > 15 mol%) to suppress the slags/steel reaction . Both strategies, however, have their advantages and drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…In recent researches, two different approaches were proposed to improve casting operation and slab surface quality . When current CaO–SiO 2 based mold fluxes with low basicity were used to cast high Al steel, spent fluxes with appropriate physical properties can ensure sufficient lubrication . However, it is difficult to avoid the chemical reactions between mold flux and liquid steel, which may cause the occurrence of cracks, depressions, and deep oscillation marks.…”
Section: Introductionmentioning
confidence: 99%
“…However, problems such as thick slag rims, inadequate slag consumption, and breakout prevention (BOP) alarms still existed, which consequently prevent long sequence casting. Furthermore, plant trials, conducted in Wuhan Iron and Steel Company Limited in 2014, showed that increasing the B 2 O 3 content in the mold flux exerted little effect on controlling slag rims and improving lubrication for the reduction of B 2 O 3 .…”
Section: Development Status Of Mold Fluxes For Continuous Casting Of mentioning
confidence: 99%